Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Recycled lithium battery nanomaterials as a sustainable nanofertilizer: Reduced peanut allergenicity and improved seed quality - Yaqi Jiang; Yi Sun; Pingfan Zhou; Guikai Zhu; Qibin Wang; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Stabilization effect of nano-SiO2@iron-phosphorus on ferrallisols, calcareous soil and organic soil heavily polluted by heavy metals: A fast reaction curing stabilization process - Zhe Yin; Qian Li; Yan Zhang; Rui Xu; Guangfei Qu; Haotian Wu; Lang Liao; Yongbin Yang; Tao Jiang (Science of The Total Environment, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Sensitive response of erosion and weathering to the Indian Summer Monsoon changes in South Asia during Dansgaard-Oeschger oscillations - Jingrui Li; Xuefa Shi; Shengfa Liu; Fangliang Li; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Thermodynamic characteristics of nitrifiers reveal the potential NOB inhibition strategies at low temperatures - Ren Li; Lifang Yu; Rui Jiang; Tian Liu; Zhuoya Li; Dangcong Peng (Journal of Cleaner Production, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Study on volatile metabolites and microbial community in the fermentation process of black tea (Jiuqu hongmei tea) - Shanshan Li; Jiaxin Huang; Xueping Chen; Rui Shen; Han Jiang; Guangfa Xie; Qi Peng (International Journal of Gastronomy and Food Science, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Efficiencies and mechanisms of remediation techniques for cationic and zwitterionic per- and polyfluoroalkyl substances (PFAS) from aqueous environments: A review - Liangdi Jiang; Rui Cao; Zhouyang Huang; Jie Jin; Ziwen Du; Haixiang Li (Chemical Engineering Journal, 2024)

Enhancing hydrothermal stability of NH3-SCR reaction over Cu-SSZ-52 catalyst by increasing Si/Al ratio - Xiangqiong Jiang; Zhifeng Zeng; Dongdong Chen; Yuyan Yao; Yang Zhang; Shuangjia Wang; Rui Li; Jiuxing Jiang (Chemical Engineering Journal, 2024)

Fabrication of magnetic Cu2O nanocomposites for enhanced iodide removal: Adsorption properties, mechanism and application - Na Jiang; Juan Bao; Tingting Zhang; Lujie Li; Lan Zhang; Weihua Li; Xianhuai Huang; Jiansheng Li; Rui Lu (Chemical Engineering Journal, 2024)

Selective regulation of products for guaiacol hydrodeoxygenation by adjusting type and acidity of supports - Min Lin; Daxin Jiang; Yuhao Yan; Lulu Zhan; Xianliang Song; Rui Li; Yulong Wu (Bioresource Technology, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

Dynamic nonparametric modeling of sail-assisted ship maneuvering motion based on GWO-KELM - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Tiancheng Wang; Zhang Ruan; Rui Zhang; Baoshen Jiang; Xiaowu Li; Jianyi Wu (Ocean Engineering, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Ultrathin PVP/ZnMoO4@PE separator for high-safety sodium-ion batteries - Siya Cheng; Qingwen He; Rui Deng; Zhi Zhang; Huanyi Liao; Yifan Zheng; Zhongxi Li; Jianing Lu; Yumeng Jiang; Yihua Gao (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

End-to-end stereo matching network with two-stage partition filtering for full-resolution depth estimation and precise localization of kiwifruit for robotic harvesting - Xudong Jing; Hanhui Jiang; Shiao Niu; Haosen Zhang; Bryan Gilbert Murengami; Zhenchao Wu; Rui Li; Chengquan Zhou; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

In situ synthesized Ag nanoparticles encapsulated inside carbonized ZIF-8 for efficient Cr(VI) reduction - Haojie Zhang; Zhuo-Rui Jiang; Yu-Xiao Zhou; Rui Chen; Hongmei Jiang; Ying Li (Journal of Environmental Chemical Engineering, 2024)

Facile synthesis of dual-functional ZIF-8-based evaporators towards high-performance in seawater desalination and uranium extraction - Zhikun Dai; Rui Gao; Qianqian Li; Mengting Qin; Jing Yang; Ran Niu; Jiang Gong (Journal of Environmental Chemical Engineering, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

Developing a radio frequency-hot air spouting treatment for efficient dehydration of carrot cubes: Evaluation of the heating and moisture distribution uniformity - Junjie Zheng; Xin Ye; Longlong Jiang; Xiaojiang Wang; Mengge Li; Yingqi Tian; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

Relationship between microorganisms and the flavour of douchi obtained from different regions: Analysis using high-throughput sequencing and GC–MS - Rui Zhang; Jing Li; Xiaoqing Miao; Zhiyuan Song; Shan Jiang; Aidong Liu (Food Bioscience, 2024)

Colorimetric sensing based on silver nanoparticle-functionalized copper porphyrin nanozyme for glyphosate - Li-Hong Yu; Rui Jiang; Cheng-Lin Yang; Yue-Hong Pang; Xiao-Fang Shen (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Electric field-driven assembly of (110) oriented metal–organic framework ZIF-8 monolayer with high hydrogen selectivity - Chunxin Jin; Shuai Liu; Rui Zheng; Yanhong Li; Xiaofang Chen; Jürgen Caro; Jianwen Jiang; Aisheng Huang (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Continuous production of pure formic acid solution from CO2 hydrogenation at room temperature via amine-functionalized PdMn nano-alloy - Xiuqin Ci; Dong Zhai; Rui Tu; Xiaoju Li; Shuchao Jiang; Xinbo Wang; Weiqiao Deng; Guoqing Ren (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Multifunctional-Element doping of NASICON-Structured cathode enables High-Rate and stable sodium storage - Xi Liu; Chengcheng Zhu; Tianhe Xu; Chang Li; Xinyu Guo; Nan Jiang; Yan Chen; Yushuang Xu; Runduo Zhu; Wenxia Zou; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2024)

Current status and impact of the Young Scientist Foundation of the National Natural Science Foundation on Chinese young scholars in cardiovascular research - Fei Gao; Zhenzhen Chen; Wendong Li; Hujun Jiang; Rui Wang (Science China Life Sciences, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Prescribed Performance Formation Tracking Control for Underactuated AUVs under Time-Varying Communication Delays - Haitian Zhang; Yanqing Jiang; Rui Gao; Hang Li; Ao Li (Journal of Marine Science and Engineering, 2024)
Achieving formation tracking control of underactuated autonomous underwater vehicles (AUVs) under communication delays presents a significant challenge. To address this challenge, a distributed prescribed performance control protocol based on a real-time state information online predictor (RSIOP) is proposed in this paper. First, we innovatively designed an RSIOP to achieve active compensation for the delayed state information of neighboring AUVs. Next, considering formation performance and safety, a low-complexity and practical nonlinear mapping function was used to implement prescribed performance tracking control for the AUV formation. Additionally, the adverse effects of external disturbance uncertainties and input saturation are also considered. Finally, the simulation tests demonstrated that the proposed formation control protocol can successfully achieve the predetermined formation tracking tasks in the presence of time-varying communication delays and external disturbances, while also enabling real-time changes in formation configuration during the process. Throughout, the protocol maintains input saturation limits, and the actual control inputs remain smooth, with no significant oscillations. Furthermore, comparative simulation tests verified the necessity of the RSIOP developed in this study and quantitatively demonstrated that the proposed control method exhibits superior performance in terms of formation control accuracy, error convergence speed, and transient-state constraints.

High-throughput proximal ground crop phenotyping systems – A comprehensive review - Z. Rui; Z. Zhang; M. Zhang; A. Azizi; C. Igathinathane; H. Cen; S. Vougioukas; H. Li; J. Zhang; Y. Jiang; X. Jiao; M. Wang; et al. (Computers and Electronics in Agriculture, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Impact of long-term conventional and biodegradable film mulching on microplastic abundance, soil structure and organic carbon in a cotton field - Kai Wang; Wei Min; Markus Flury; Anna Gunina; Jun Lv; Qiang Li; Rui Jiang (Environmental Pollution, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Global health benefits of shipping emission reduction in early 2020 - Wenwen Sun; Wenxin Jiang; Rui Li (Atmospheric Environment, 2024)

Correction: Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)

Ceftriaxone Modulates Ubiquitination of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid Receptors to Improve Long-Term Potentiation Impairment Induced by Exogenous β-Amyloid in a Glutamate Transporter-1 Dependent Manner - Rui Jiang; Li Li; Bu Wang; Lizhe Liu; Lirong Liu; Xiaohui Xian; Wenbin Li (Molecular Neurobiology, 2024)

Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)
The pathogenesis and development of Moyamoya disease are still unclear. This study aimed to investigate the effect of desmoglein-2 (DSG2) on Moyamoya disease and determine the inhibitory effect of DSG2 in vascular remodeling in Moyamoya disease. RNA sequencing, immunohistochemistry (IHC), and western blotting were used to detect the expression of DSG2 in the superficial temporal artery (STA) tissues of Moyamoya disease. The association between DSG2 and endothelial cells’ biological activities was investigated by cell counting kit-8 (CCK-8), migration assay, tube formation assay, flow cytometry with Annexin V-FITC/PI staining, and TUNEL apoptotic cell detection kit. Pathways affected by overexpression or knockdown of DSG2 were identified in endothelial cells. The expression of DSG2 in the STA tissues of Moyamoya disease was lower than that in normal controls. Overexpression of DSG2 inhibits the proliferation and migration but promotes apoptosis in endothelial cells, and low DSG2 levels result in impaired angiogenesis. In addition, there was an interaction between DSG2 and MMP-9, and DSG2 acted through the PI3K signaling in endothelial cells. Our results indicate that DSG2 affects PI3K signaling in vascular endothelial cells, and MMP-9 is involved in DSG2-mediated vascular changes in Moyamoya disease.

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Green Approach for Simultaneous Quantitative Analysis of Fluoroquinolones in the Environment using Three-Dimensional Fluorescence Coupled with Second-Order Calibration Method - Yuping Yao; Liyan Song; Lingli Jiang; Mengfan Sun; Rui Li; Zhongze Zhou; Yuanna Li (Journal of Fluorescence, 2024)

Stress mitigation mechanism of rice leaf microbiota amid atmospheric deposition of heavy metals - Hanbing Gao; Zhaohui Guo; Xiao He; Jinbo Yang; Li Jiang; Aiping Yang; Xiyuan Xiao; Rui Xu (Chemosphere, 2024)

Utilizing oxygen-rich vacancies in Bi2O2CO3/ZnFe2O4 heterojunction photocatalytic materials for the efficient degradation of tetracycline hydrochloride in water - Hongqing He; Xianbin Li; Shunzhi Li; Weiwei Zhu; Rui Jiang; Zhiwei Zhai; Yang Cao (Journal of Water Process Engineering, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Developing a spouted bed for combined radio frequency-hot air treatments to improve the heating uniformity in high-moisture carrot cubes - Junjie Zheng; Longlong Jiang; Xin Ye; Xiaojiang Wang; Yingqi Tian; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Effect of BaTiO3 as a filling material with adjustable dielectric properties on improving the radio frequency heating uniformity in red jujubes - Longlong Jiang; Junjie Zheng; Mengge Li; Yingqi Tian; Xiaojiang Wang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

From characteristics to practical applications of skin temperature in thermal comfort research – A comprehensive review - Jiaqi Zhao; Rui Wang; Yeyu Wu; Chaoyi Zhao; Yun Qi; Sishi Li; Haihua Jiang; Bin Cao (Building and Environment, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Oxygen vacancies-promoted removal of COS via catalytic hydrolysis over CuTiO2-δ nanoflowers - Xiaohai Zheng; Rui Huang; Bang Li; Weiping Jiang; Lijuan Shen; Ganchang Lei; Yingying Zhan; Shiping Wang; Lilong Jiang (Chemical Engineering Journal, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Physiological and molecular mechanism of Populus pseudo-cathayana × Populus deltoides response to Hyphantria cunea - Yutong Ding; Jiajia Shen; Hanxi Li; Yue Sun; Tingbo Jiang; Xiangbo Kong; Rui Han; Chunli Zhao; Xinxin Zhang; Xiyang Zhao (Pesticide Biochemistry and Physiology, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Highspeed transport pathway dominated by continuous arrangement of micron-sized hollow MOFs in MMMs to accelerate CO2 permeation - Wenji Zheng; Rui Ding; Ziheng Li; Xuehua Ruan; Yan Dai; Miao Yu; Xiangcun Li; Xiaoming Yan; Xiaobin Jiang; Xiujuan Zhang; Gaohong He (Chemical Engineering Journal, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

Loss in the rare bacterial diversity drives the monocropping obstacle of cut chrysanthemum - Jun Li; Feng Meng; Niannian Chen; Maibo Jiang; Guixin Chu; Rui Tao (Journal of Soil Science and Plant Nutrition, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Morphological estimation of primary branch length of individual apple trees during the deciduous period in modern orchard based on PointNet++ - Xiaoming Sun; Leilei He; Hanhui Jiang; Rui Li; Wulan Mao; Dong Zhang; Yaqoob Majeed; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

H5N1 high pathogenicity avian influenza virus in migratory birds exhibiting low pathogenicity in mallards increases its risk of transmission and spread in poultry - Qiuyan Mao; Zhixin Li; Yuecheng Li; Yaxin Zhang; Shuo Liu; Xin Yin; Cheng Peng; Rui Ma; Jinping Li; Guangyu Hou; Wenming Jiang; Hualei Liu (Veterinary Microbiology, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Records of deep-sea turbidity current activity in the Bengal Fan since the Last Glacial Maximum - Jingrui Li; Xin Shan; Xuefa Shi; Shengfa Liu; Shuqing Qiao; Hui Zhang; Kaikai Wu; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Performance enhancement, bacterial communities optimization and emerging pollutants elimination by microalgal-bacterial consortium for treating aquaculture pond sediments - Xuda Wang; Shilei Li; Rui Mi; Ying Dong; Jingwei Jiang; Xiaoyan Guan; Xiaoyue Wang; Bo Ye; Danni Liu; Zhenjun Zhao; Xuewen Gao; Zunchun Zhou (Journal of Environmental Management, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Automated segmentation of individual leafy potato stems after canopy consolidation using YOLOv8x with spatial and spectral features for UAV-based dense crop identification - Hanhui Jiang; Bryan Gilbert Murengami; Liguo Jiang; Chi Chen; Ciaran Johnson; Fernando Auat Cheein; Spyros Fountas; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

Modeling and design of fed-batch strategies for achieving 255 g/L sugar concentration from high-solid enzymatic hydrolysis of pretreated corn stover - Haixiang Li; Rui Zhai; Xiangxue Chen; Xiaoxiao Jiang; Chen Li; Qiufeng Deng; Zhaoxian Xu; Mingjie Jin (Chemical Engineering Journal, 2024)

Losses of low‐germinating, slow‐growing species prevent grassland composition recovery from nutrient amendment - Zhongling Yang; Junyong Li; Rui Xiao; Chunhui Zhang; Xiaojun Ma; Guozhen Du; Guoyong Li; Lin Jiang (Global Change Biology, 2024)
Nutrient enrichment often alters the biomass and species composition of plant communities, but the extent to which these changes are reversible after the cessation of nutrient addition is not well‐understood. Our 22‐year experiment (15 years for nutrient addition and 7 years for recovery), conducted in an alpine meadow, showed that soil nitrogen concentration and pH recovered rapidly after cessation of nutrient addition. However, this was not accompanied by a full recovery of plant community composition. An incomplete recovery in plant diversity and a directional shift in species composition from grass dominance to forb dominance were observed 7 years after the nutrient addition ended. Strikingy, the historically dominant sedges with low germination rate and slow growth rate and nitrogen‐fixing legumes with low germination rate were unable to re‐establish after nutrient addition ceased. By contrast, rapid recovery of aboveground biomass was observed after nutrient cessation as the increase in forb biomass only partially compensated for the decline in grass biomass. These results indicate that anthropogenic nutrient input can have long‐lasting effects on the structure, but not the soil chemistry and plant biomass, of grassland communities, and that the recovery of soil chemical properties and plant biomass does not necessarily guarantee the restoration of plant community structure. These findings have important implications for the management and recovery of grassland communities, many of which are experiencing alterations in resource input.

Feedback regulation of plant secondary metabolism: Applications and challenges - Chuhan Li; Rui Jiang; Xingxing Wang; Zongyou Lv; Wankui Li; Wansheng Chen (Plant Science, 2024)

Analysis of factors affecting the performance of air gun source under shallow water conditions: Insights from the non-ideal gas air gun wavelet model - Mingxin Zhao; Jiangbo Huang; Cai Li; Jiang Li; Jiangfeng Zheng; Rui Han; Huaishan Liu (Ocean Engineering, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Developing a two-stage strategy in the dehydration treatment of fresh apple slices: Combined freeze and radio frequency-vacuum drying - Xiaojiang Wang; Dingting Zhou; Mengge Li; Junjie Zheng; Longlong Jiang; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Suspended sediment dynamics and linking with watershed surface characteristics in a karst region - Linlv Xiao; Rui Li; Jun Jing; Jiang Yuan; Zhengyi Tang (Journal of Hydrology, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Modulating surface zinc species via facet engineering for efficient electroreduction of CO2 to CO - Junjie Wang; Zhaozhao Zhu; Yingxi Lin; Xueqiang Qi; Zhao Li; Jinxia Jiang; Xiaobin Niu; Jun Song Chen; Rui Wu (Chemical Engineering Journal, 2024)

Constructing novel deep eutectic composites based on hydrogen bond network as anode material for lithium-ion batteries - Yiting Wang; Yifei Li; Jiali Chai; Qingmeng Li; Jiakai Du; Yichuan Rui; Bohejin Tang; Lei Jiang (Chemical Engineering Journal, 2024)

Temperature–Controlled hydrothermal hydrogenation of palmitic acid to alkanol or alkanes over Co@CN–x catalysts derived from ZIF–67 - Min Lin; Daxin Jiang; Yuhao Yan; Xiaoxian Li; Lulu zhan; Xianliang Song; Rui Li; Yulong Wu (Chemical Engineering Journal, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Prediction interaction responses between railway subgrade and shield tunnelling using machine learning with sparrow search algorithm - Xiang Liu; Kuichen Li; Annan Jiang; Qian Fang; Rui Zhang (Transportation Geotechnics, 2024)

The decomposition of algae has a greater impact on heavy metal transformation in freshwater lake sediments than that of macrophytes - Si-Min Xue; Shu-Qi Jiang; Rui-Ze Li; Yi-Ying Jiao; Qun Kang; Li-Ya Zhao; Zhao-hua Li; Mo Chen (Science of The Total Environment, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Performance analysis of the comprehensive energy system based on active energy storage-discharge technology under time-sharing electricity price operation strategy - Dong Zhang; Yuzhan Jiang; Shaohua Wang; Haoran Li; Jianhua Bai; Rui Zhang; Zhoujian An (Journal of Cleaner Production, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Harnessing synergy: Integrating agricultural waste and nanomaterials for enhanced sustainability - Yuying Tang; Weichen Zhao; Li Gao; Guikai Zhu; Yaqi Jiang; Yukui Rui; Peng Zhang (Environmental Pollution, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)